SISTEM PENGELOLAAN SAMPAH DI RUMAH SAKIT UMUM DAERAH TGK. CHIK DITIRO SIGLI KABUPATEN PIDIE - T. Khairol Razi; Fadli Syahputra; Muhammad Azhari; Aswadi Aswadi (Jurnal Sosial Humaniora Sigli, 2022)
Hospital sanitation efforts are one of the supporting efforts in providing health services. Meanwhile, one of the hospital sanitation efforts is hospital waste management efforts (Permenkes No. 1204/Menkes/SK/X/2004). This research is descriptive with a cross-sectional design, where the author wants to know the description of the waste management system at the Tgk Regional General Hospital. Chik Ditiro Sigli, Pidie Regency in 2020. Sorting medical and non-medical waste at the Tgk Regional General Hospital. Chik Ditiro Sigli, Pidie Regency, Each room is separated and has a lid that is intact and easy to open, but the trash cans also have a plastic bag color according to the specified symbol and the garbage collection is made of materials that are not easy to rust, strong and water-resistant so that they are easy to clean and emptied, the shelter is resistant to sharp and pointed objects so that transportation is also available for transporting carts/garbage trolleys with a flat bottom surface and watertight so that the waste does not stick to the means of transportation and does not become a nest of insects, but the transportation of waste is transported to the TPS 2 times a day and to the TPA every day and garbage storage has a complete and open lid, the garbage storage place is also far from the Tgk Chik Ditiro Sigli General Hospital space agency, Pidie Regency and medical waste collection is carried out 24 hours a day and storage is according to the tropical climate, maximum during the rainy season. 48 hours of rain and a maximum of 24 dry season hours but the Tgk Chik Ditiro Sigli General Hospital, Pidie Regency does not have a waste disposal site, waste destruction is carried out or cooperates with a 3rd party PT. Cahaya Tanjung Tiram and final waste disposal, non-medical waste in collaboration with the Sanitation Department and do not destroy medical waste every day so that from the overall results of direct observations in the field. Based on the results of research on the Waste Management System at the Tgk Regional General Hospital. Chik Di Tiro Sigli, Pidie Regency in 2020 consisting of 59 samples or the entire room, the results that meet the requirements are 57 sample units or 96.61% while those who do not meet the requirements are 2 sample units or equal to 3.39%. Keywords: Waste Management, Hospital